2018
DOI: 10.1016/j.jhsa.2018.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Injection Into the First Dorsal Compartment: A Cadaveric Ultrasound Study

Abstract: Ultrasound is unlikely to increase the accuracy of injections into an unseptated FDC. It may aid in injection of a septated FDC; however, that remains to be statistically demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…After cutaneous penetration, the needle is directed parallel to the forearm beneath the extensor retinaculum and the injectate is delivered. 13 In the present study, the authors demonstrated that ultrasound-guided steroid injections conferred significantly better outcomes over manual injection techniques, both in terms of injection accuracy as assessed by anatomical studies, 14,21,22 and clinical cure rates. 26,[39][40][41][42][43][44][45] In a study directly comparing both approaches, a 91 percent clinical success rate, defined as the avoidance of surgery, was reported for the ultrasound-guided injection group and a 59 percent success rate was reported for the manual injection group.…”
Section: Discussionmentioning
confidence: 52%
“…After cutaneous penetration, the needle is directed parallel to the forearm beneath the extensor retinaculum and the injectate is delivered. 13 In the present study, the authors demonstrated that ultrasound-guided steroid injections conferred significantly better outcomes over manual injection techniques, both in terms of injection accuracy as assessed by anatomical studies, 14,21,22 and clinical cure rates. 26,[39][40][41][42][43][44][45] In a study directly comparing both approaches, a 91 percent clinical success rate, defined as the avoidance of surgery, was reported for the ultrasound-guided injection group and a 59 percent success rate was reported for the manual injection group.…”
Section: Discussionmentioning
confidence: 52%
“…In the presence of a septum, the USG group achieved a higher infiltration rate in EPB sub-compartments of 75% accuracy in reaching the sub-compartment when compared to 33% in AL. Although statistically unconfirmed, they stated that USG aided injections in the presence of a septum [32]. In our series, more than 50% of patients had a separate sub-compartment and none of them came back with recurrence of symptoms, suggesting the effectiveness of USG guided injections.…”
Section: Relevance and Importance Of Ultrasound For Steroid Injectionsmentioning
confidence: 45%
“…Another study, by Kang et al in a series of 15 fresh cadavers, demonstrated not only a higher accuracy for USG guided injections (93.3% vs. 40%) to target the first extensor compartment but also better results when separate septum was present (85.7% vs. 16.7%) [30]. In a cadaver model involving 43 specimens comparing USG and anatomical landmark (AL) guided injection, Kutsikovich et al showed that both techniques had an infiltration rate of 100% [32]. In the presence of a septum, the USG group achieved a higher infiltration rate in EPB sub-compartments of 75% accuracy in reaching the sub-compartment when compared to 33% in AL.…”
Section: Relevance and Importance Of Ultrasound For Steroid Injectionsmentioning
confidence: 99%
See 2 more Smart Citations